Pharmacology and therapeutic potential of agarwood and agarwood tree leaves in periodontitis - Xie, Chen; Dong, Jing-Zhe; Lu, Bing-Shuai; Yan, Peng-Yao; Zhao, Yun-Shan; Ding, Xin-Yue; Lv, Cheng-En; Zheng, Xu (Frontiers in Pharmacology, 2024)
The main bioactive components of agarwood, derived from Aquilaria sinensis, include sesquiterpenes, 2-(2-phenethyl) chromone derivatives, aromatic compounds, and fatty acids, which typically exert anti-inflammatory, antioxidant, immune-modulating, hypoglycemic, and antitumor pharmacological effects in the form of essential oils. Agarwood tree leaves, rich in flavonoids, 2-(2phenethyl) chromone compounds, and flavonoid compounds, also exhibit significant antiinflammatory, antioxidant, and immune-modulating effects. These properties are particularly relevant to the treatment of periodontitis, given that inflammatory responses, oxidative stress, and immune dysregulation are key pathological mechanisms of the disease, highlighting the substantial potential of agarwood and agarwood tree leaves in this therapeutic area. However, the low solubility and poor bioavailability of essential oils present challenges that necessitate the development of improved active formulations. In this review, we will introduce the bioactive components, extraction methods, pharmacological actions, and clinical applications of agarwood and agarwood tree leaves, analyzing its prospects for the treatment of periodontitis.